Three-dimensional vibration control of high-tech facilities against earthquakes and microvibration using hybrid platform. - Hong, Xiao-Jian (Earthquake engineering & structural dynamics.)
High-tech equipments engaged in the production of ultra-precision products have very stringent vibration criteria for their functionality in normal operation conditions and their safety during an earthquake. Most previous investigations were based on simplified planar models of building structures, despite the fact that real ground motions and structures are always three-dimensional. This paper hence presents a three-dimensional analytical study of a hybrid platform on which high-tech equipments are mounted for their vibration mitigation. The design methodology of the hybrid platform proposed in this study is based on dual-level performance objectives for high-tech equipments : safety against seismic hazard and functionality against traffic-induced microvibration. The passive devices (represented by springs and viscous dampers) and the active actuators are designed, respectively, to meet vibration criteria corresponding to safety level and functionality level. A prototype three-story building with high-tech equipments installed on the second floor is selected in the case study to evaluate the effectiveness of the hybrid platform. The optimal location of the platform on the second building floor is determined during the design procedure in terms of the minimal H2 cost function of absolute velocity response. The simulation of the coupled actuator-platform-building system subjected to three dimensional ground motions indicates that the optimally designed hybrid platform can well achieve the dual target performance and effectively mitigate vibration at both ground motion levels.